IMPROVING EQUIPMENT FOR DRYING FRUIT AND VEGETABLE RAW MATERIALS USING RENEWABLE ENERGY SOURCES - Omelchenko , O. V.; Tsvirkun , L. О.; Perekrest, V. V.; Korin , K. O. (Systems and Technologies, 2026)
The article states that the food industry plays a key role in the global demand for food products, while significantly affecting energy consumption and the state of the environment. Therefore, the primary task of the food industry should be to transition to a green course, namely, the reduction or recycling of waste heat in order to reduce energy consumption and control green house gas emissions. Analysis of scientific sources showed that recently energy-efficient technologies based on renewable energy sources have been used, namely heat pumps in the drying process of plant raw materials. An effective drying system is substantiated to reduce energy consumption, as well as minimize deterioration in the quality of dried products based on active heat recovery methods. A structural diagram of the drying process with a heat pump using forced convection, operating in a closed environment with full recirculation of dried air, is proposed. It is considered appropriate to consider a drying system with a heat pump as an interaction of three subsystems, the first of which is responsible for the drying chamber – a set of elements involved in the movement of air, where heated air circulates, passes through the raw material, picks up moisture and transfers it to the evaporator of the heat pump. This subsystem is considered as an open subsystem due to the exchange of energy with the heat pump. The second subsystem is a closed subsystem operating in a closed air circuit, where only energy exchange in the form of heat occurs through its boundaries, while moist air is not lost, but recirculated. The second subsystem includes a heat pump, the main elements of which are a compressor, condenser, evaporator and expansion valve. The third subsystem provides control of the drying process, which requires the installation of humidity and temperature sensors inside the drying chamber at the inlet to the evaporator and at the outlet from the condenser. The ability to transfer heat from one subsystem to another is a key factor in achieving optimization of energy consumption in the drying process. This allows for high drying efficiency using a heat pump and high quality of the resulting dried raw materials.